Current views on adhesive bonding systems - Łukomska-Szymańska, Monika; Sokołowski, Jerzy; Łapińska, Barbara (Journal of Stomatology, 2017)
Dental bonding systems are flowable resin-based materials, that produce indirect adhesive layer. These materials are applied to bond composite material to prepared surface of enamel and/or dentine. Reliable bonding of direct and indirect dental restoration to tooth structures depends on the proper choice of adhesive strategy corresponding with morphology of hard dental tissues. The aim of the article is to present the development of dental bonding systems and their bonding mechanism to enamel and dentine. Nowadays, universal multi-mode bonding systems gain growing popularity among dental practitioners due to simplified application procedure and versatile clinical indications, including bonding to glass and zirconia ceramics or metal. Yet, the bond strength of these universal adhesives to hard dental tissues may vary depending on their composition and adhesive mode used. Given all abovementioned aspects of performance, clinicians must carefully consider the choice of dental adhesives to achieve the best desirable clinical effect of the restorative treatment.